Prognostic significance of pre-operative C-reactive protein and the neutrophil–lymphocyte ratio in resectable pancreatic cancer: a systematic review. Issue 4 (April 2015) - Stevens, Lewis; Pathak, Samir; Nunes, Quentin M.; Pandanaboyana, Sanjay; Macutkiewicz, Christian; Smart, Neil; Smith, Andrew M.
Abstract: Background: Better pre-operative risk stratification may improve patient selection for pancreatic resection in pancreatic cancer. C-reactive protein (CRP) and the neutrophil–lymphocyte ratio (NLR) have demonstrated prognostic value in some cancers. The role of CRP and NLR in predicting outcome in pancreatic cancer after curative resection is not well established. Methods: An electronic search of MEDLINE, EMBASE and CINAHL was performed to identify studies assessing survival in patients after pancreatic cancer resection with high or low pre-operative CRP or NLR. Systematic review was undertaken using the PRISMA protocol. Results: In total, 327 studies were identified with 10 reporting on survival outcomes after a pancreatic resection in patients with high or low CRP, NLR or both. All but one paper showed a trend of lower inflammatory markers in patients with longer survival. Three studies from six showed low CRP to be independently associated with increased survival and two studies of eight showed the same for NLR. All studies were retrospective cohort studies of low to moderate quality. Discussion: Inflammatory markers might prove useful guides to the management of resectable pancreatic cancer but, given the poor quality of evidence, further longitudinal studies are required before incorporating pre-operative inflammatory markers into clinical decision making.